REGULATORY T CELLS AND THE MICROENVIRONMENT OF THE MALIGNANT B CELL OF CHRONIC LYMPHOCYTIC LEUKEMIA - Georgiana Ene; Ana Maria Vlădăreanu; Horia Bumbea; Ion Dumitru (Romanian Medical Journal, 2019)
In recent years understanding and modulating the tumor microenvironment (MT) has been the focus of a scientifically and clinically intense study. The role of T regulatory cells (Tregs) were investigated in terms of the suppression of tumor-specific immune responses and the establishment of an immunosuppressive tumor microenvironment (1). Regulatory T cells have a fundamental function in maintaining immune homeostasis in healthy individuals, and in cancer and in particular in haematological malignancies they seem to play a rather controversial role. Furthermore an increased frequency of Treg cells has been associated with tumor progression and has been correlated with an increased risk of death and reduced survival (2). The role of T cells in the pathogenesis of chronic lymphocytic leukemia has recently gained special attention due to the constant interaction between neoplastic B cells with the micromedium substrate and T cells. There is often a relatively large number of regulatory T cells in lymphoid tissues of CLL patients, that could affect the normal immune function (3).